Collision Detection for Flexible Link Robots using Accelerometers. Issue 16 (2019) - Pucher, Florian; Gattringer, Hubert; Müller, Andreas
Abstract: For a robot operating in unknown environment, fast detection of occurring collisions is mandatory in order to react accordingly. This is especially the case when robots are interacting with humans. For this application area often lightweight robots are used to decrease the damage potential. Resulting link vibrations can be met with vibration damping control by the use of acceleration sensors. When already equipped for control applications, the accelerometers can also be used for detecting link collisions. A method for collision detection with acceleration sensors based on joint torque estimation is presented and compared to a generalized momentum observer which is frequently used for this purpose, as can be found in literature. The methods are compared in an experiment on a three-degrees-of-freedom (3-DOF) robot with flexible links where the contact force is measured additionally.